Hellenismen i Ægypten - Giversen, Søren (Religionsvidenskabeligt Tidsskrift, 1990)
The strong Greek influence on cultural development in Ptolemaic Egypt during the reign of the first kings of the Ptolemaic dynasty was later partly substituted by a stronger Egyptian influence. This is hown with examples from selected areas such as language, calendar, law, administration, communication and religious matters.